Preparation of shape memory PCL/CB composites and its photo-triggered bending deformation behaviors - TIAN Guangming; ZHANG Xin; LI Mingcai; TANG Wenqiang; MA Jianhua; YANG Dong (Xi'an Gongcheng Daxue xuebao)
In order to prepare shape memory polymers with remote controllable deformation and superior performance, PCL/CB composites were prepared by thiol-ene click chemistry method, and their chemical structures, thermal properties and shape memory properties were characterized via FTIR, DSC, 1H NMR and DMA. The results indicate that the thermal transition temperature is 50 ℃, and when the pre-stretched composite film is irradiated by a 100 mW/cm2 laser, the CB particles absorb laser photons and produce photothermal conversion. Due to the relaxation of the anisotropic chain and the release of strain energy, the upper layer shrinks due to the melting of crystal regions when irradiated with laser, while the lower layer is still in a glassy state. The shrinkage force of the upper film causes the PCL/CB composite material film to bend and deform toward the direction of laser irradiation. At the same time, the bending angle can be controlled by three parameters: pre-stretch strain, irradiation time, and film thickness. When the prestretch strain is 300% and the film thickness is 0.4 mm, the maximum bending angle is 164°. The PCL/CB composite film with locally programmable behavior can provide new ideas for the deformation mode of light responsive SMP.